NANOSPHERE-LOADED TADALAFIL WITH ENHANCED ORAL BIOAVAILABILITY: INNOVATIVE APPLICATION OF ELECTROHYDRODYNAMIC TECHNIQUE - MEHANNA, MOHAMMED M.; ALWATTAR, JANA K. (International Journal of Current Pharmaceutical Research, 2020)
Objective: Electrohydrodynamic atomization is a technique that utilizes electrical potential differences for the fabrication of particles ranging from nano to micrometer size, where the ultra-charged droplets of drug-loaded mist deposit as nanospheres after solvent evaporation. The drug-loaded polymeric spherical nanocomposites have a small volume with large surface area, which is a beneficial characteristic for dissolution and bioavailability enhancement of class II drugs. Methods: This facile approach is employed for the preparation of tadalafil-loaded nanosystems, a class II drug used for erectile dysfunction treatment. Tadalafil-loaded nanoparticles prepared with different polymer concentrations were evaluated through process yield, drug loading, morphology and functional performance. Further, drug solid-state and compatibility of formulation components were assessed. Results: The results obtained pointed out that nanoparticles were of uniform spherical morphologies with a size range between 1279±141 and 374±13 nm. The system maintained a high loading efficacy of 88%, with most of the loaded drug released within 2 min during the in vitro dissolution studies. The differential scanning calorimetry, X-ray diffraction and Fourier-transform infrared spectroscopy demonstrated the presence of tadalafil in an amorphous form or as a molecular dispersion within the polymer matrix. Conclusion: Tadalafil-loaded nanoparticles manufactured through this methodology is qualified as a strategy to ameliorate its solubility and bioavailability.